Sustainable construction materials for low-cost housing: Thermal insulation potential of expanded SBR composites with leather waste - Ribeiro, Gabriel Deltrejo [UNESP]; Hiranobe, Carlos Toshiyuki [UNESP]; Araújo, Samara da Silva [UNESP]; Filgueira, Matheus da Silva [UNESP]; Rocha, José Afonso [UNESP]; Mukuno, Jefferson Shiguemi [UNESP]; Salmazo, Leandra Oliveira; Gomes, Andressa Silva [UNESP]; Tolosa, Gabrieli Roefero [UNESP]; Gennaro, Elmer Mateus; Job, Aldo Eloizo [UNESP]; Pérez, Miguel Angel Rodríguez; et al. (Elsevier, 2024)
In recent years, there has been a growing interest in improving energy efficiency and thermal comfort in low-income housing, especially in regions prone to extreme climatic conditions. Conventional construction materials such as bricks and concrete exhibit shortcomings in energy efficiency, resulting in high indoor temperatures. This scenario not only impacts residents' well-being but also increases energy consumption, especially for air conditioning systems, potentially straining the electrical infrastructure in hot climate areas, leading to power outages and adverse consequences for the community and local industry. This study proposes an innovative and sustainable solution: the use of expanded styrene-butadiene rubber (SBR) with micronized leather shavings, possessing thermal insulation properties. The thermal insulation capacity of the composites was evaluated using heat flow methods, hot/cold plate heat flow analysis, and impedance tube acoustic method. The SBR/Leather waste composite at 20 phr emerges as a viable, promising, and sustainable alternative, exhibiting significant thermal insulation capacity with a thermal conductivity of 0.073 Wm-1.K−1 and temperature attenuation close to 15 °C, potentially enhancing comfort and quality of life in urban areas. The thermal insulation results of the other composites also surpassed traditional construction materials such as building boards, plywood, fiberglass, asphalt roofing, and cement tiles. The study demonstrates the feasibility of reusing leather as a reinforcing filler in rubber-based foams to produce thermal insulation materials, offering a sustainable solution to mitigate urban heating and improve quality of life in cities.
Keywords: Expanded SBR rubber; Leather waste; Sound insulation; Thermal conductivity; Thermal insulation